Areview of the effects of stannous fluoride on gingivitis (Blackwell Synergy, 2006)
Aim: To review the literature on the effects of stannous fluoride on gingivitis. Material and Methods: The Medline and cochrane central register of controlled trials were searched up to August 2005 to identify appropriate studies. The primary outcome measure was gingivitis. Results: Independent screening of titles and abstracts of 542 papers resulted in 36 publications (inter-reviewer eË† score of 0.76), out of which 15 papers finally fulfilled the criteria of eligibility. For SnF2 dentifrices, a statistically significant reduction in gingivitis was noted in comparison with control (weighted mean difference (WMD) of 0.15 (gingival index) and 0.21 (gingivitis severity index) (test for heterogeneity po0.00001, I2591.1% and p50.03, I2580.1%, respectively)). With regard to plaque reduction inconsistent results existed. On using the plaque index no differences were found, whereas meta-analysis of the Turesky index provided a WMD of 0.31 (p50.01, test for heterogeneity po0.0001, I2591.7%). Because of insufficient data, a meta-analysis for SnF2 mouth rinse and dentifrice/mouthrinse formulations was not performed. Conclusions: The use of SnF2 dentifrices results in gingivitis and plaque reduction when compared with a conventional dentifrice. The precise magnitude of this effect was difficult to assess because of a high level of heterogeneity in study outcomes.